Perampasan Aset sebagai Bentuk Upaya Pemiskinan Kepada Pelaku Tindak Pidana Korupsi - Zainudin Hasan; Aisyah Habibah Azra; Sindy Ramadhani; Maretha Lintang Putri Praptisia (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2025)
Current efforts to eradicate corruption are not only focused on arresting and imposing criminal sanctions on perpetrators, but also through efforts to restore the country's financial and economic losses by confiscating assets or property belonging to perpetrators of corruption. Asset recovery or confiscation of assets from perpetrators of corruption is an important thing that must be considered in handling corruption cases, as a form of recovery of state losses. Therefore, there must be a good policy formulation to support the implementation of asset recovery. Indonesia needs special regulations or rules that have legal force and have special rules regarding the mechanism for confiscating assets and property suspected of being obtained from the proceeds of corruption. This study is entitled Asset Confiscation as a Form of Punishment for Perpetrators of Corruption. The purpose of this study is to determine and explain legal policies related to asset confiscation.